E-067 Verapamil and its association with hives in radial artery catheterization for neuroendovascular diagnostic angiograms. (23rd July 2022) - Romeo, D; Salem, M; Burkhardt, J; Jankowitz, B
Abstract : Introduction: Different combinations of medications are utilized during radial artery (RA) catheterization for neuroendovascular procedures to preclude RA spasm. These combinations commonly include verapamil, a calcium channel blocker among the 'radial cocktail', without established benefit in mitigating the risk of RA spasm. However, the negative effects of verapamil such as the acute development of hives are sparsely reported in the context of RA neuro-angiography. We sought to assess their association using a case-control cohort of our single center experience. Methods: A series of consecutive patients undergoing diagnostic radial angiograms were reviewed and analyzed. Patients who had verapamil in their medication cocktail were classified as 'cases' and patients without verapamil were 'controls'. We limited the analysis to diagnostic angiograms, excluding treatment procedures to avoid potential confounding factors such as the complexity of a given treatment. The primary outcomes assessed were the presence of hives and radial artery spasm. Results: 215 radial diagnostic neuro-angiography procedures were included in our analysis. 137 patients underwent RA catherization with verapamil and 84 underwent RA catherization without verapamil. Of the 137 patients that received verapamil, 4 (2.9%) developed hives during the RA catherization procedure and were subsequently treated with Benadryl (25 mg) and 0 (0.0%) experienced RA vasospasm. Of the 78 who did not receive verapamil, there were 0 (0.0%) cases of hives and 1 (1.3%) case of RA spasm. Conclusion: The administration of verapamil for those undergoing RA vasospasm appears to be associated with the development of hives without significant reduction in the RA spasm risk. More data is needed to better understand the utility and safety of verapamil in RA catherization procedures. Disclosures: D. Romeo: None. M. Salem: None. J. Burkhardt: None. B. Jankowitz: None.